Proses Pengendalian Kualitas Produk Reject dalam Kualitas Kontrol PT. Yasufuku Indonesia Bekasi - Aprilia Puspasari; Dede Mustomi; Erlina Anggraeni (Universitas Bina Sarana Informatika, 2019)
Quality control on reject products at PT. Yasufuku Indonesia in Bekasi is quite good, because it is in accordance with the theory of quality control, at least reject products can be minimized. Documents that are available are functioning properly by HR and the functions of the relevant division are still not maximal in carrying out their duties and authority in quality control in reject products. There are still obstacles. Machine factors that cause the production of goods with reject short material, incomplete documents that hamper the production process goods, as well as unintentional errors in data recording and processing, the solutions that have been made by PT. Yasufuku Indonesia in overcoming these obstacles is as follows: Provide guidance on the types of raw materials to users so that users understand the types of raw materials needed and separate the place of raw materials by type, Make a different identity or lot card for each type of raw material production , from the identity color or lot card and the place where the identity or lot card is separated each type, Solution to overcome unintentional errors in the production process of goods so that the product is rejected because of several factors including creating work instructions and installing them on each table or production machine and giving directives to all machine users to follow the standards of the machine production process procedures.